Tutors’ Experiences and Perceptions of a Problem-based Learning Approach in an ESL Writing Classroom - Muhammad Mukhtar Aliyu (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2019)
This study investigated tutors’ experiences and perceptions of using a problem-based learning approach (PBL) in an ESL writing classroom. The participants of the study are two Nigerian tutors who facilitated an intact class of 18 second-year students in an English composition course which lasted for 12 weeks. Data were collected through semi-structured interviews. The tutors were interviewed after the implementation of the PBL process. The overall findings of the study show that the tutors have positive perceptions of the use of PBL in a writing classroom. Specifically, the findings reveal the tutors’ positive experiences and perception of the workshop conducted prior to the PBL process, the ill-structured problems presented to the students, tutor facilitation and students’ group activities. Finally, the paper gives some pedagogical implications which would give insight for better implementation of the PBL approach.